Anemia em população de área endêmica de malária, Rondônia (Brasil) Anaemia in a population sample from an endemic malaria area of Rondônia State, Brazil - Marly A. Cardoso; Marcelo U. Ferreira; Luís M. Aranha Camargo; Sophia C. Szarfarc (Universidade de São Paulo, 1992)
Com o objetivo de descrever a prevalência de anemia na população de uma área endêmica de malária - o distrito de Candeias, localidade periurbana do Município de Porto Velho, no Estado de Rondônia, Amazônia Ocidental Brasileira, - uma amostra casual de 1.068 indivíduos (14,1% da população total) de todas as idades submeteu-se à dosagem de hemoglobina e à microscopia em gota espessa para diagnóstico de malária. O diagnóstico de anemia foi positivo em 299 indivíduos (28,0% da amostra), sendo as maiores prevalências encontradas em crianças com idade entre 6 meses e um ano (70,0%) e entre um e 6 anos (38,4%), além de gestantes (41,2%), 7/17) e pacientes com malária (44,4%, 8/18). Realizaram-se exames parasitológicos de fazes em amostra voluntária de 476 indivíduos (44,6% da população amostral), dos quais 118 (26,3%) foram positivos. Nessa amostra voluntária, não houve diferença significante na prevalência de anemia entre indivíduos parasitados e não-parasitados. Acima de 14 anos de idade, a prevalência de anemia foi tanto maior quanto mais recente o último episódio de malária referido pelos pacientes. Nesta faixa etária, economicamente produtiva, destaca-se o papel da malária entre as causas subjacentes à anemia. With the purpose of describing the prevalence rate of anaemia among inhabitants of a malaria endemic area - Candeias district, a periurban locality near Porto Velho, in Rondônia State, Brazilian Amazon Basin - a random population sample comprehending 1,068 individuals of all age groups (14.1% of the total population) was screened for anaemia (measurement of blood haemoglobin concentration) and malaria (Giemsa-stained thick-smear microscopy). Two-hundred and ninety-nine individuals (28.0% of the sample) were found to be anaemic, using the cut-off haemoglobin values proposed by the World Health Organization for each age group. Highest prevalence rates were found among children with ages varying from 6 months to 1 year (70.0%) and from 1 to 6 years (38.4%), as well as in pregnant women (41.2%, 7/17) and malaria patients (44.4%, 8/18). Parasitological stoll examinations were made on a voluntary sample of 476 individuals (44.6% of the sample population); of these, 118 (26.8%) were positive. Eggs of Ascaris lumbricoides, the most frequent intestinal parasite in this population sample, was detected in 67 stool samples (14.1%); only 27 patients (5.7%) eliminated Ancylostomidae eggs. In this voluntary sample, no significant difference in anaemia prevalence rates between parasite carriers and non-parasited individuals was detected. On the other hand, the more recent the last malarial episode referred to by the patients, the ligher prevalence rate of anaemia in individuals above the age of 14 years. The role played by malaria as an underlying cause of anaemia in Candeias district inhabitants, particularly in the economically active age group, is further discussed.